Stuart Wood and the Marginal Productivity Theory - Stigler, George J. (Quarterly Journal of Economics, 1947)
Journal Article Stuart Wood and the Marginal Productivity Theory Get access George J. Stigler George J. Stigler Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 61, Issue 4, August 1947, Pages 640–649, https://doi.org/10.2307/1885053 Published: 01 August 1947